2012
DOI: 10.3109/13651501.2011.644563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the validity of the Chinese versions of the Hypomania Symptom Checklist-32 (HCL-32) and Mood Disorder Questionnaire (MDQ) for the detection of bipolar disorder in medicated patients with major depressive disorder

Abstract: The results of our study demonstrate that the HCL-32 and MDQ are of reasonable validity to distinguish between bipolar disorder and major depressive disorder. However small sample size may limit generalization of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Supporting lower specificity and higher sensitivity of HSL-32 compared with MDQ in diagnosing BD,52,53 our findings indicate HSL-32 and MDQ to reveal the likelihood of comorbid BD in 100.0% and 91.3% of patients, respectively, with confirmed diagnosis, while HSL-32 also revealed positive results in 70.1% of patients without BD. In fact, unipolar depressed patients have been suggested to have clinical features that resemble the type II BD patients in the presence of migraine, possibly indicating that migraine in depressed patients is a bipolar spectrum trait 54.…”
Section: Discussionmentioning
confidence: 55%
“…Supporting lower specificity and higher sensitivity of HSL-32 compared with MDQ in diagnosing BD,52,53 our findings indicate HSL-32 and MDQ to reveal the likelihood of comorbid BD in 100.0% and 91.3% of patients, respectively, with confirmed diagnosis, while HSL-32 also revealed positive results in 70.1% of patients without BD. In fact, unipolar depressed patients have been suggested to have clinical features that resemble the type II BD patients in the presence of migraine, possibly indicating that migraine in depressed patients is a bipolar spectrum trait 54.…”
Section: Discussionmentioning
confidence: 55%
“…All of them showed similar overall screening qualities of the two tests, and sensitivity of HCL-32 was always slightly higher [25–30]. …”
Section: Introductionmentioning
confidence: 99%
“…This fundamental conceptual error in determining a cutoff score on bipolar disorder screening scales on the basis of optimal agreement with a diagnostic standard has continued in more recent studies. I reviewed 27 recently published studies that examined the performance of bipolar disorder screening scales across a range of scores (Bech, Christensen, Vinberg, Bech-Andersen, & Kessing, 2011;Boschloo et al, 2013;Chou et al, 2012;Cyprien et al, 2014;de Sousa Gurgel et al, 2012;Feng et al, 2016;Frey, Simpson, Wright, & Steiner, 2012;Gamma et al, 2013;Gan et al, 2012;Hsieh et al, 2016;Hu et al, 2012;Imamura et al, 2015;Kung et al, 2015;Leao & Del Porto, 2012;Lee et al, 2013Lee et al, , 2016Mosolov et al, 2014;Nallet et al, 2013;Pan & Yeh, 2015;Perugi et al, 2012;Poon, Chung, Tso, Chang, & Tang, 2012;Sasdelli et al, 2013;Smith et al, 2011;Waleeprakhon et al, 2014;Yang et al, 2014;Yang et al, 2011;Zaratiegui et al, 2011). Almost every study recommended a cutoff point on the screening scale that maximized or optimized the level of agreement with the diagnostic gold standard.…”
Section: Selecting a Cutoff Score On A Screening Testmentioning
confidence: 99%
“…They concluded that the MDQ "is suitable to screen for bipolar disorder in clinical settings" (p. 5). Chou et al (2012) examined the performance of the HCL and MDQ in psychiatric outpatients. They conducted an ROC analysis and at the recommended cutoff point found that the HCL had a sensitivity of 100% and specificity of 46%, and the MDQ had a sensitivity of 71% and specificity of 77%.…”
Section: Researchers' Conclusion Regarding the Clinical Utility Of Bmentioning
confidence: 99%